The Future of Uruguayan Surgery: A Possible Utopia? - Carriquiry, Luis A (Cirugía del Uruguay, 2002)
When Luis Russian asked me that the Society I wanted to reserve one day in the year for each one of the Surgical Clinics of the Faculty and that aspired for one of the presentations to be a lecture by the Professor of the Clinic, it occurred to me almost immediately that more interesting to carry out an updated tune-up of some of the surgical topics of my preference, it could be to make some conceptual contribution on the status of our surgery, throwing ideas matured in countless desk discussions and corridor with colleagues from the Surgical Clinic «2», with the neighbors, with the other teachers of Surgery and even with foreign visitors and filtered by the cerno of reflection about from my experience in academic surgical practice and mutual